Precision-based exercise in people with anxiety and stress related disorders: Are there interindividual differences in anxiolytic effects? An ancillary meta-analysis of randomized controlled trials. (November 2022) - Vancampfort, Davy; Heissel, Andreas; Waclawovsky, Aline; Stubbs, Brendon; Firth, Joseph; McGrath, Ryan L.; Van Damme, Tine; Schuch, Felipe B.
Highlights: There is no evidence for interindividual differences in anxiolytic effects of exercise in people with anxiety and stress-related disorders. Clinical practice can focus on general exercise guidelines for patients with anxiety- and stress-related disorders rather than aiming for highly specific, individualized recommendations. Abstract: Interest in the individualized responses to exercise has been growing within mental health care and psychiatry. This meta-analysis examined if true interindividual differences (IIDs) in anxiolytic effects of exercise exist among adults with anxiety- and stress-related disorders. Data were extracted from a previous meta-analysis of randomized controlled trials (RCTs) and searches in CINAHL, Embase and Medline were updated (8 arms from 7 original studies, n participants=322). Change outcome standard deviations treated as point estimates for anxiety were extracted to calculate true IIDs. Inverse variance heterogeneity and restricted maximum likelihood models were used. Aerobic exercise and resistance training showed significant anxiolytic effects. No significant pooled IIDs were found for aerobic exercise nor resistance training demonstrating that there is currently a lack of convincing evidence to support the notion that true IIDs exist for the anxiolytic effects of exercise among adults with anxiety- and stress-related disorders. Consequently, clinical practice can focus on general population physical activity guidelines for patients with anxiety- and stress-related disorders rather than aiming for highly specific, individualized recommendations. Future research could prioritize investigating how to motivate patients with anxiety- and stress-related disorders to meet general population physical activity guidelines.